A composite material of vacuum heat-treated CQDs/Ce0.7Zr0.3O2 with enhanced charge separation for efficient photocatalytic degradation. (November 2019) - Gao, Xing; Nguyen, Tat Thang; Gong, Xinchao; Chen, Xueqi; Song, Zihui; Du, Wenxin; Chai, Rusong; Guo, Minghui
Abstract: In this study, Cex Zr1−x O2 solid-solution oxide (x = 0.7) was prepared using hydrothermal method, and the obtained Ce0.7 Zr0.3 O2 nanoparticles were modified with wood–based carbon quantum dots (CQDs). Furthermore, we report a composite photocatalyst of vacuum heat-treated CQDs/Ce0.7 Zr0.3 O2 for degrading methylene blue. The structural properties and photocatalytic activity of CQDs/Ce0.7 Zr0.3 O2 were systematically studied after vacuum heat treatment. Herein, a part of the functional groups present on CQD surfaces changed through high–temperature heating during vacuum heat treatment. The dominant structures sp 2 hybrid carbon atoms and amorphous carbon were transformed to defect states of sp 3 hybrid oxygen atoms, thus increasing the surface oxygen vacancy concentration. The high activity and excellent stability of vacuum heat-treated CQDs/Ce0.7 Zr0.3 O2 system can be attributed to increased surface oxygen vacancy concentration, modification of CQDs, and the protruding structure of Ce0.7 Zr0.3 O2, contributing to efficient charge transfer. This study provides potential systems of CQD-modified photocatalysts and also reveals the substantial effect of vacuum heat treatment on enhancing the photocatalytic properties of composites. Graphical abstract: Image 1 Highlights: A novel composite material of vacuum heat-treated CQDs/Ce0.7 Zr0.3 O2 is synthesized. The photocatalytic property of the vacuum heat-treated CQDs/Ce0.7 Zr0.3 O2 is examined. The CQDs/Ce0.7 Zr0.3 O2 shows an enhanced activity after vacuum heat treatment. Vacuum heat treatment increases surface oxygen vacancy concentration in composites. It facilitates to enhance charge separation for efficient photocatalytic degradation.